The roots, the branches and the fruits: exploring the impact of brazilian student entrepreneurship societies on startup creation and on entrepreneurship education - Guerreiro, Fernando; Ferrari, Roberto (Journal of Management and Business Education, 2023)
<span style="color: #333333; font-family: 'Open Sans', Helvetica, Arial, sans-serif; font-size: 15px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Student Entrepreneurship Societies (SES) are bottom-up organizations, led and developed by university students to promote entrepreneurship and innovation practices. This paper reports results of research aimed to survey the Brazilian SES, characterizing their main activities, challenges, supporters, and how SES are impacting startup creation and the development of entrepreneurship skills among students. We identified the Brazilian SES, applied two questionnaires to gather information about the SES and interviewed some SES leaders. We found 92 SES in Brazil. Only 3,7% of the 2608 Brazilian Universities were linked to a SES, and the 940 students directly involved in SES represent only 0,01% of the 8.03 million Brazilian university students. In the UK such proportion is considerably higher - 1,2%. SES members study Canvas Business Model, pitch, MVP, Design Thinking and Lean Startup; they promote talks, workshops, networking events, hackathons, and business plan competitions. They develop practical projects essentially in all areas and receive support from professors, entrepreneurs, startups, investors and other agents of the ecosystem. Although SES leaders have reported participation and/or support in the creation of 24 startups, only 8 (28,57% from 28 respondent SES) had records on startup creation. Through involvement in SES, the student’s education is enriched by theory and practice, networking, and influence from professors, entrepreneurs, startup communities and other students. The positive impact of SES on a student’s professional development should motivate policy makers, startup communities, investors and universities to consider increasing support to SES. New research should be conducted to shed light on the impact of SES for the creation of new businesses.